SYNTHESIS AND CHARACTERIZATION OF GRAPHENE OXIDE USING LIQUID PHASE EXFOLIATION (LPE) DAN HUMMER’S METHOD: MINI REVIEW - Duratulhikmah, Nur Fadhilah; Hindryawati, Noor; Syaima, Husna (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Graphene oxide (GO) is a 2D material that has various oxygen functional groups on its surface and edges. The existence of these clusters makes GO have enormous potential to be applied in various fields. Currently various methods have been developed to synthesize these materials including Liquid Phase Exfoliation (LPE) and Hummer's. This review will present the synthesis of Graphene oxide along with the results of its characterization using Fourier Transform Infra Red (FTIR), Raman Spectroscopy, and UV-Vis spectrophotometer. Literature results show that in FTIR the typical functional groups that will appear are the O-H, C=O, and C-O epoxy groups, on Raman spectroscopy it shows peaks of 1300-1400 cm-1 (D-band) and peaks of 1500-1600 cm-1 (G -band) and there is a maximum absorption peak value at a wavelength of 200-235 nm from the results of UV-Vis characterization Keywords: Graphene Oxide, Hummer’s, Liquid Phase Exfoliation, Raman Spectroscopy